2023
DOI: 10.3390/ph16040541
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Molecular Hydrogen in Metabolic Diseases from Bench to Bedside

Abstract: Oxidative stress and chronic inflammation have been implicated in the pathophysiology of metabolic diseases, including diabetes mellitus (DM), metabolic syndrome (MS), fatty liver (FL), atherosclerosis (AS), and obesity. Molecular hydrogen (H2) has long been considered a physiologically inert gas. In the last two decades, accumulating evidence from pre-clinical and clinical studies has indicated that H2 may act as an antioxidant to exert therapeutic and preventive effects on various disorders, including metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 108 publications
0
3
0
Order By: Relevance
“…Up to now, no intervention studies with H 2 have been reported in CKD patients. However, regarding CKD risk factors, such as diabetes mellitus (DM), metabolic syndrome, and hypertension, six clinical trials were reported to explore the potentials of H 2 [89]. Among them, three studies may indicate the potential reno-protective effect, i.e., decreased oxidative stress marker and/or increased antioxidants in urine, by drinking hydrogen-rich water.…”
Section: Clinical Studies Of H 2 Intervention In Related To Ckd Patho...mentioning
confidence: 99%
“…Up to now, no intervention studies with H 2 have been reported in CKD patients. However, regarding CKD risk factors, such as diabetes mellitus (DM), metabolic syndrome, and hypertension, six clinical trials were reported to explore the potentials of H 2 [89]. Among them, three studies may indicate the potential reno-protective effect, i.e., decreased oxidative stress marker and/or increased antioxidants in urine, by drinking hydrogen-rich water.…”
Section: Clinical Studies Of H 2 Intervention In Related To Ckd Patho...mentioning
confidence: 99%
“…The protective effect of H 2 on diabetes and its complications may be associated with the inhibition of oxidative stress, inflammation, apoptosis, activation of the mitochondrial ATP-sensitive potassium (Mito-K-ATP) pathway, etc. [107].…”
Section: Effects Of H 2 On Metabolic Syndromementioning
confidence: 99%
“…The latest findings in medical research regarding hydrogen unequivocally highlight substantial prospects for harnessing hydrogen as a therapeutic intervention. Extensive observations in both clinical and experimental studies distinctly demonstrate that hydrogen holds significant promise as an innovative therapy to address unmet patient needs across various etiologies [1][2][3][4][5][6][7][8][9][10]. Renowned for its antioxidant properties, hydrogen gas has emerged as a novel therapeutic agent with potential applications in various medical domains, including transplantation.…”
Section: Introductionmentioning
confidence: 99%